CHALLENGES IN MANAGING THE REPRODUCTIVE CELL DONATION PROGRAM PROCESS IN SERBIA - Djordjević, Biljana; Šurlan, Lela; Mitrović Jovanović, Ana; Petrović, Dejan (HEALTH CARE, 2026)
Introduction/Aim: This study examines the governance challenges in Serbia’s egg and sperm donation system. The necessity of donors importing donated reproductive cells requires coordination among clinics, regulatory agencies, and international tissue banks. The main objective is to analyse the roles, responsibilities of key institutions and stakeholders in the donation program, exploring opportunities for system improvement through clinical alignment and analysis of implementation in Fertility clinics. Methods: A descriptive statistical method was applied to the data collected using a questionnaire sent to IVF clinics, utilising the Resposinble, Accoutable, Consulted and Informed (RACI) matrix to define institutional roles, and conducting a Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis based on the RACI matrix results. Results: RACI analysis revealed that the Ministry of Health bears the highest number of information responsibilities, confirming its leading, regulatory, and supervisory role. Based on the questionnaire, Clinical Embryologists handle most documentation tasks, including packaging and shipping (47.1%) and communication with tissue banks (58.8%). Most respondents (41.2%) reported that documentation errors rarely occur, while non-compliances from foreign banks were very uncommon (70.6%), and the Ministry’s institutional support was viewed as limited. Conclusion: The results highlight a system with unclear and limited strategic communication, utilising the RACI matrix, which proved to be useful in clarifying institutional roles. The SWOT analysis emphasised both strengths (professional capacity) and threats, highlighting that excessive centralisation of roles can overload an institution and slow down processes. Future research should focus on quantitative analyses of clinical outcomes related to the origin and quality of donated material, as well as comparative evaluations of communication between institutions, banks and regulatory bodies.